If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(8 + -1x) + x = 36 + x (8 * 6 + -1x * 6) + x = 36 + x (48 + -6x) + x = 36 + x Combine like terms: -6x + x = -5x 48 + -5x = 36 + x Solving 48 + -5x = 36 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 48 + -5x + -1x = 36 + x + -1x Combine like terms: -5x + -1x = -6x 48 + -6x = 36 + x + -1x Combine like terms: x + -1x = 0 48 + -6x = 36 + 0 48 + -6x = 36 Add '-48' to each side of the equation. 48 + -48 + -6x = 36 + -48 Combine like terms: 48 + -48 = 0 0 + -6x = 36 + -48 -6x = 36 + -48 Combine like terms: 36 + -48 = -12 -6x = -12 Divide each side by '-6'. x = 2 Simplifying x = 2
| 14x^2+9x^2= | | (2x^3)*(5x^6)= | | 10a+6c= | | 4(8-5x)=-2 | | 1.8(5x+4)=3.4 | | 25*x=1000 | | 1.5(3r-4)=2.5 | | 10-3x+33=12 | | 0=x-2y+2 | | 2y^2+y+3x+8=0 | | 5(x-4)=-2(x-3)+7 | | 4x+18=360 | | 5-3y=15 | | y=-2x+b | | 3-3y=15 | | 1-3y=15 | | 5-2y=4 | | 4-w=11 | | 6(5-2x)-2(7-x)=2x | | 4m+2n+9m+7n= | | 6.8x+2.7=8 | | 54x^2-39x+5=0 | | 4+5y=20 | | 55=11+2(n-1) | | (24x+18x)+8=40x+2x | | (24x+18x)+8=40x+2c | | 3(24x+18x)=40x+2x | | 5a+10c= | | (24x+18x)3=40x+2x | | 21c^2=6c | | (24x+18x)3=6x(7x) | | 87x-3=(50x+37x) |